Cognitively and physically demanding exergaming to improve executive functions of children with attention deficit hyperactivity disorder: a randomised clinical trial. Issue 1 (December 2017) - Benzing, Valentin; Schmidt, Mirko
Abstract Background Attention deficit hyperactivity disorder (ADHD) is one of the most common mental disorders observed in childhood and adolescence. Its key symptoms — reduced attention, poor control of impulses as well as increased motor activity — are associated with decreased executive functions performance, finally affecting academic achievement. Although drug treatments usually show some effect, alternative treatments are continually being sought, due to lack of commitment and possible side effects. Cognitive trainings are frequently used with the objectives of increasing executive function performance. However, since transfer effects are limited and novelty and diversity are frequently ignored, interventions combining physical and cognitive demands targeting a broader range of cognitive processes are demanded. Methods The aim of the study is to examine the effects of a cognitively and physically demanding exergame on executive functions of children with ADHD. In a randomised clinical trial, 66 girls and boys diagnosed with ADHD (age 8–12) will be assigned either to an 8-week exergame intervention group (three training sessions per week à 30 min) or a waiting-list control group. Before and afterwards, the executive function performance (computer-based tests), the sport motor performance and ADHD symptoms will be assessed. Discussion The current study will offer insights into the effectiveness of a combination of cognitive and physical training using exergaming. Positive effects on the executive functions, sport motor performance and ADHD symptoms are hypothesized. Beneficial effects would mean a large degree of scalability (simple and cost-effective) and high utility for patients with ADHD. Trial registration KEK BE 393/15 (March 8, 2016);DRKS00010171 (March 14, 2016)